The flightless period of the Mallard in England - Boyd, Hugh (Wildfowl, 1961)
Captures of flying and flightless Mallard in cage-traps at Abberton, Essex and of flightless Mallard at Slimbridge confirm that the timing of the wing-moult in males and females in England is similar to that found in Holland. Flightless males are found from early June to mid-August, females from late June to September and occasionally October. The spread of the female moult is due to variation in individual breeding success, females normally not moulting until their young are fledged. From records of ringed males of known age it appears that males one and two years old tend to become flightless ahead of the majority of older birds.